BUDIDAYA MAGGOT DALAM PENINGKATAN KEWIRAUSAHAAN DI KELURAHAN GUNUNG LINGAI - Agus Riyanto; Lisda Amara Dewi; Nur Anggi Andini (Wadah Inovasi Indonesia, 2022)
This PKM (Community Service) activity was carried out with a number of people who live in the Gunung Lingai District area to be precise on Jalan Gunung Lingai, Berkat Gang. PKM activities are carried out by providing maggot cultivation entrepreneurship training materials and providing directions to residents. It is hoped that the people who live on Jalan Gunung Lingai Gang Berkat have sufficient knowledge and expertise to cultivate animal feed (maggot) as a substitute for factory processed feed. This will allow citizens to earn more money from the maggot cultivation business.